INTRODUCTORY TEXTBOOK OF Psychiatry - Black, Donald W. 1956-; Andreasen, Nancy C. (American Psychiatric Association Publishing, 2021)
The Introductory Textbook of Psychiatry provides a comprehensive introduction to the field both for students new to psychiatry and for students who are studying for their board exams. This authoritative, seventh edition has been thoroughly updated to reflect advances since the last edition. DSM-5® provides a frame for the text's many illuminating clinical vignettes, which in turn bring diagnosis, assessment, and treatment to vivid life. Other features, such as clinical points, self-assessment questions, and an exhaustive glossary of terms, add to the educational value and enhance learning. The internationally renowned authors have produced a text of uniform approach and uncommon style, and readers will appreciate the insight and rigor that have made the Introductory Textbook of Psychiatry the bestselling volume of its kind for more than two decades.